IGREJA DE CRISTO PENTECOSTAL NO BRASIL fundação, re(d)ação e teologia no contexto brasileiro de 1934 a 1986 - Silva, Wallace de Góis (2015)
The proposal of this study is to investigate the understanding of the role of the Church and its faithful in the world, according to the publications of the Pentecostal Church of Christ in Bra-zil (ICPB) and to interpret the results in dialogue with the social, cultural, economical, reli-gious and political context of Brazil at the time. As period we propose the years 1935-1986, which includes the time of ministry of the founders, Horace and Carolyn Ward, Chester and Rachel Miller and Annie and Russel Frew, from the United States; the time of Ernst Grimm, an Estonian preacher; and the time of José Pinto de Oliveira, the first Brazilian elected general superintendent. The emphasis in these personalities also becomes plausible as they have been during the timespan under investigation the main church writers or authors of the texts to be interpreted in this work. The hypothesis of this work is that a growing awareness for social is-sues can be related to the rise of a Brazilian leadership. Although this dynamic is interrupted with the emergence of the military dictatorship in 1964, it is resumed in the late seventies of the last century. As method we propose to analyze the theological and doctrinal teaching found in official publications of the ICPB, such as their official journals, Brazilian and Ameri-can, its book editions, Sunday School material, minutes of its general conventions and books and notes or drafts written by the pioneers above mentioned. We conclude that the theologies and context analyzes found in the publications, justify a more diverse understanding: first, it can be shown, in religious and political terms, that existed a greater proximity between the views expressed by the authors and more conservative (or even reactionary) currents of the country. On the other hand, we identified aside of this dominant discourse a dissonant ap-proach with the potential to serve as a starting point for a more significant engagement in the society by the ICPB and its membership, including the denunciation of socioeconomic injus-tice, and that the respective discourses are pronounced more among national leaders.